The effect of different doctrines between the litigants in the civil lawsuit on the judge's return to the principles of Islamic law - Musa, Karim Mohammed Kazim; Abbas, Mahdi Salih; Mohamed, Fadel Radi; Talib, Zainab Kazem (International Journal of Psychosocial Rehabilitation, 2020)
The Iraqi legislator has created several sources that the trial court must follow to resolve the disputes that arise when it ruled the cases brought to it, as the first item of the first subject of ((Iraqi Civil Law No. (40) for the year 1951 (amended))) made the legislative text is the first of these sources, according to the second item of the subject and the law themselves, the custom comes secondly in the absence of the aforementioned text, the Iraqi legislator obliged the court of issue to judge the case before it in the absence of these two sources by following the principles of Islamic Sharia which are most appropriate to the texts of the Iraqi civil law to resolve that conflict without being restricted by a certain doctrine, where the Iraqi society can consist of multiple Islamic schools of thought, the most prominent of which are five schools of thought, the first four of which are called (the public or the people of the public) which they are (Hanafi, Maliki, Shafi’i and Hanbali) also the term (Jaafari or Imamiya) is called on the fifth doctrine, on this basis, when a dispute arose before the trial court between two people of two different doctrines, as there was no legislative text judging it, as there was no knowing moral to apply on it, The court must then extract the legal rule by referring to the principles of Islamic law, provided that the rule is derived from the most appropriate principles of the provisions of the Iraqi civil law, that the court does not adhere to a specific doctrine to settle this dispute, so this means that the judge is obliged to extract a legal rule that judge the dispute between registration and release.